2022
DOI: 10.7759/cureus.22272
|View full text |Cite
|
Sign up to set email alerts
|

CYP4F22-Related Autosomal Recessive Congenital Ichthyosis: Clinical Presentation

Abstract: Autosomal recessive congenital ichthyosis (ARCI) is a group of hereditary, nonsyndromic disorders of keratinization. ARCI encompasses several different clinical presentations and is caused by various genetic mutations. Commonly, ARCI presents with a taut, thick, shiny stratum corneum called a collodion membrane, but patients with mutations in CYP4F22 frequently present only with erythroderma. We report the case of a patient who was heterozygous for a pathogenic variant and a variant of uncertain significance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…Dumenigo et al reported a case of CYP4F22-related ARCI with bilateral chalazion and punctate keratopathy. 4 These reports, in conjunction with our case, suggest that multiple ocular manifestations may be more common in individuals with CYP4F22 mutations; however, further studies are needed to substantiate this correlation.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Dumenigo et al reported a case of CYP4F22-related ARCI with bilateral chalazion and punctate keratopathy. 4 These reports, in conjunction with our case, suggest that multiple ocular manifestations may be more common in individuals with CYP4F22 mutations; however, further studies are needed to substantiate this correlation.…”
supporting
confidence: 68%
“…At 3-month follow-up, parents reported improvement of scaling (Figure 2 CYP4F22 is a rare genetic mutation responsible for 8% of cases of ARCI. 4 Our report of the novel mutation c.529 C>T variant increases known pathogenic CYP4F22 variants to the literature.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Most patients with a CYP4F22 mutation are born with marked erythroderma without a collodion membrane, hyperlinearity of palms and soles, and desquamation on the scalp. 9 Mutations that lead to loss-of-function of filaggrin, a structure protein involved in skin barrier function cause IV, predispose to AD and may act as modifiers in other forms of ichthyosis. 10,11 Recently a case of ARCI -CYP4F22 was reported to respond well to therapy with ustekinumab.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Die meisten Patienten mit einer CYP4F22-Mutation werden mit einer ausgeprägten Erythrodermie ohne Kollodiummembran, einer Hyperlinearität der Handflächen und Fußsohlen sowie einer Schuppung der Kopfhaut geboren. 9 Mutationen, die zu einem Funktionsverlust von Filaggrin führen, verursachen IV, prädisponieren für AD und können als Modifikatoren bei anderen Formen der Ichthyose wirken. 10,11 Kürzlich wurde von einem Fall von ARCI -CYP4F22 berichtet, der gut auf die Therapie mit Ustekinumab ansprach.…”
unclassified